The Differentiated Parent Support Model: Enhancing the Involvement of Parents Who Do Not Speak the School Language - MacPhee, Mary (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
Despite 40 years of research indicating that parent involvement is important for student achievement, schools have done little to engage parents across Canada. This study and model recommend strategies to enhance the probability of educational involvement for parents who do not speak the school language. The mixed methods research with surveys (N = 86) and interviews (N = 38) identified the successes and challenges of non-francophone parents with children in French minority-language schools. Parents wanted to help but struggled with French schoolwork and school-community involvement. Parents’ low French proficiency and low school effort to facilitate parent communication and comprehension were some of the barriers that led to a decreased sense of parent autonomy and competency. Policy and practices by educators and parent-groups can encourage involvement and support parents in a French minority-language population as they overcome language and insecurity barriers at home or school. The findings can be generalized to support parent involvement in other multilingual contexts.